2010
DOI: 10.1029/2009jd011943
|View full text |Cite
|
Sign up to set email alerts
|

Macrophysical and optical properties of midlatitude cirrus clouds from four ground‐based lidars and collocated CALIOP observations

Abstract: [1] Ground-based lidar and Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) data sets gathered over four midlatitude sites, two U.S. and two French sites, are used to evaluate the consistency of cloud macrophysical and optical property climatologies that can be derived by such data sets. The consistency in average cloud height (both base and top height) between the CALIOP and ground data sets ranges from −0.4 km to +0.5 km. The cloud geometrical thickness distributions vary significantly between the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 51 publications
2
46
1
Order By: Relevance
“…The CALIOP 532 nm channel is known to be accurately calibrated (Rogers et al, 2011), and a number of previous studies have shown that the performance of the CALIPSO layer detection scheme is consistent with the predictions and limitations described in the project's algorithm theoretical basis document (Vaughan et al, 2005;McGill et al, 2007;Dupont et al, 2010;Thorsen et al, 2011;Yorks et al, 2011). Although there are few systematic studies of CALIOP's aerosol subtyping reported in the literature, the available comparisons suggest that the CALIOP scheme is successful ∼70 % of the time; the best agreement occurs for dust, and the least agreement occurs for aerosol layers dominated by the fine mode (Mielonen et al, 2009).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 74%
“…The CALIOP 532 nm channel is known to be accurately calibrated (Rogers et al, 2011), and a number of previous studies have shown that the performance of the CALIPSO layer detection scheme is consistent with the predictions and limitations described in the project's algorithm theoretical basis document (Vaughan et al, 2005;McGill et al, 2007;Dupont et al, 2010;Thorsen et al, 2011;Yorks et al, 2011). Although there are few systematic studies of CALIOP's aerosol subtyping reported in the literature, the available comparisons suggest that the CALIOP scheme is successful ∼70 % of the time; the best agreement occurs for dust, and the least agreement occurs for aerosol layers dominated by the fine mode (Mielonen et al, 2009).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 74%
“…The fundamental sampling resolution of the lidar is 30 m vertical and 335 m horizontal. The high quality of processed CALIPSO data products has been demonstrated through validation campaigns (Winker et al, 2007;Vaughan et al, 2008) and comparisons studies with ground-based instruments (Plana-Fattori et al, 2009;Dupont et al, 2010;Thorsen et al, 2011). In this study, we compare the regional quality of climatological cirrus cloud properties from CALIOP to those observed from the ground-based lidar at the OHP.…”
Section: Caliop Spaceborne Lidarmentioning
confidence: 99%
“…In an area 100 km wide, CALIOP will only sample twice per 16 day repeat cycle, providing 45 sampling opportunities per year. Extending the domain to a 2 • × 6 • latitude-longitude box yields 300 (day + night) overpasses with about 45 samples each, resulting in about 14 000 samples (as in Dupont et al, 2010). Temperature used through the paper in relation with CALIOP data come from the GEOS-5 general circulation model reanalyses, which are included in CALIOP data files.…”
Section: Caliop Spaceborne Lidarmentioning
confidence: 99%
“…There are a couple of recent studies on the properties of cirrus clouds at midlatitudes based on ground-based lidar observations (Dupont et al, 2010;Hoareau et al, 2013;Dionisi et al, 2013). The analyses show a significant and large proportion of optically thin cirrus clouds in the upper troposphere (42 % of all profiles, Hoareau et al, 2013), in the tropopause region (30 % of all and 9 % of the cloudy profiles, Dionisi et al, 2013), or, even more precisely localised, above the tropopause (up 10 % of all cloudy profiles, Rolf, 2013 , the cloud measurements show 5 % cross-tropopause cirrus (cloud base below and cloud top above the tropopause) and 2 % inter-tropopause (cloud base above tropopause) events.…”
Section: Comparison With Ground-based Lidar Measurementsmentioning
confidence: 99%